The Development of Augmented Reality Learning Media for Human Blood Circulatory System Materials to Strengthen the Motivation of Elementary School Students - Magfiroh, Kholishotul; Winahyu, Sri Estu; Thohir, M.Anas (Caruban: Jurnal Ilmiah Ilmu Pendidikan Dasar, 2024)
Augmented Reality (AR) media is a future media to connect something abstract into be real. However, it is rarely used in elementary schools, especially the science content of human circulatory system material. This research aims to produce AR-based learning media products that are valid according to media experts, valid according to material experts, practical according to practitioners (teachers) and users (students), and effective in strengthening student learning motivation. The research and development (R&D) method of the ADDIE model was used in this research and development. The assessment results from various parties show that augmented reality learning media can be used in learning. The average result of expert validation received a score of 90% with a very valid category based on the assessment of media validators , media validators 2,and material validators. The practicality test obtained an average score of 93.8% with a very practical category based on practitioners and users in small group trials and field trials. The effectiveness test results were obtained at 94% (observer) with a very effective category. The results of the effectiveness of the pre-test and post-test of the student motivation questionnaire get an average percentage from 48.8% to 90.6% which shows very effective. The N-Gain test obtained 2.77 with a very effective category. Thus, augmented reality learning media on human circulatory system material is suitable to use in strengthening the learning motivation of grade V elementary school students.